Avaliação de placas de radiografia computadorizada para a geração de imagens de mama - Mabel Bustos Flores (2017)
Breast cancer is the second cancer type with the highest incidence among women and the estimate of new cases of breast cancer in Brazil by 2016 is more than 57 thousand, according to the National Cancer Institute. Mammography is the imaging technique most used worldwide for the early diagnosis of breast cancer. Computed radiography plates (CR) are used for digital radiography, and are widely used in Brazil to obtain digital mammograms. This work aims to evaluate the response of CR plates to the variation of exposure in mammography equipment. Three CR plates for mammography of different models were used for the study. X-ray beams were selected to perform successive exposures of CR plates by varying the exposure time. These exposures were performed to obtain raw images and to measure the air kerma incident on the CR plate using a Unfors Xi meter. The digital images were analyzed using the ImageJ software, in which the value of intensity recorded in the central region of each image was correlated with the exposure time. From these data the necessary correlations were made to determine the exposure time and air kerma incident for which the CR plate begins to saturate by observing that the saturation occurs first for the highest value of the applied voltage. Subsequently the analysis of the entire image area was performed to determine the percentage variation of the recorded intensity and the maximum and minimum intensity, observing that this percentage variation is smaller the longer the exposure time and the applied voltage. Finally, successive exposures of the CR plate were made using the compressed breast simulator made of acrylic plates and microcalcifications of different sizes to determine the resolution of CR plates, observing that only microcalcifications above 177 m are visible in the image. The knowledge of saturation characteristics and resolution of the CR plate allows the selection of more adequate parameters to work without approaching the saturation region